3Ts of low cure rate: taxonomy, themes and theory of low cure rate in Pakistan's TB control programme and gathering a 360-degree perspective through qualitative, in-depth interviewing approach. Issue 7 (9th July 2019) - Ali, Syed Mustafa; Hussain, Sumaira; Ishaq, Muhammad; Ali, Shoukat; Naureen, Farah; Noor, Arif; Rashid, Aamna; Anjum, Naveed
Abstract : Objective: WHO recommends cure of tuberculosis (TB) as the best prevention strategy; however, information about factors associated with low cure rate in patients with drug-susceptible TB is limited in Pakistan. Therefore, the purpose of this study was to explore the factors that account for low TB cure rate. Methodology: The present qualitative study recruited diverse informants through purposive sampling to explore low cure rate situation in Badin between March and June 2017. Data were collected from clinicians, paramedics, lab technicians, district field supervisors, patients and treatment supporters through indepth and face-to-face interviews. Interviews were conducted in local languages (Urdu and Sindhi) and transcribed into English. Coding structure was developed inductively and applied on textual data to draw output at the levels of taxonomy, themes and theory, as proposed by Bradley et al . Findings: Thirty-seven individuals consented to participate in this study and provided detailed account of the subject under enquiry. Review of interview data collected from a variety of informants resulted in the identification of four broad factors (taxonomy) that contributed to the situation of low cure rate in one of the districts implementing the public–private mix intervention. These factors were (1) health-seeking behaviour, (2) technical capacity of the healthcare provider, (3) managerial capacity of the healthcare provider, and (4) access to healthcare facility and services. Each factor is deconstructed into key dimensions (themes) that emerged from the dialogue between the interviewer and the respondents. Moreover, dimensions were exemplified through underlying concepts that correspond to theories for low cure rate. Conclusion: Change in programme reporting requirement has demeaned the significance of having cure as treatment outcome. Therefore, returning the focus to achieving cure status for TB cases will be beneficial for assessing the effectiveness of TB control efforts. In parallel to the care delivery system, a mechanism for disseminating disease-related and treatment-related information should be introduced.